THE EFFECT OF RGEC COMPONENTS ON THE SHARE PRICE OF BANKING SECTOR COMPANIES - Tri Kartika Sari; Linawati Linawati; Erna Puspita (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research is motivated by a significant decline in banking stock prices in 2024, triggered by the end of the credit restructuring stimulus by the OJK and the massive sell-off by foreign investors. This condition raises concerns about increasing credit risks and declining market confidence. Therefore, this study aims to analyze the influence of bank health factors using the RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital) approach. The variables used include Risk Profile (NPL), GCG (Self Assessment), Earning (NIM), and Capital (CAR) on the share price of banking companies listed on the Indonesia Stock Exchange for the 2022–2024 period. The research method used was a quantitative approach with purposive sampling techniques, resulting in 32 banking companies as a sample during three years of observation. Data analysis was carried out using classical assumption tests, multiple linear regression, determination coefficient tests, and hypothesis tests with  SPSS software version 30. The results of the study showed that partially, GCG, NIM, and CAR had a significant effect on stock prices, while NPLs had no significant influence. Simultaneously, all components of RGEC have a significant effect on the share price of banking companies.